ON THE RECOVERY OF TEMPORAL VARIATIONS OF GEOID HEIGHTS DETERMINED WITH THE USE OF GGMS BASED ON SST-HL DATA FROM NON-DEDICATED GRAVITY SATELLITE MISSIONS - Godah, Walyeldeen; Szelachowska, Malgorzata; Krynski, Jan (Boletim de Ciências Geodésicas, 2020)
Over 15 years the Gravity Recovery and Climate Experiment (GRACE) had considerably contributed to the determination of temporal variations of geoid heights. In May 2018, GRACE Follow-On (GRACE-FO) was launched. The aim of this contribution is to assess the suitability of data from non-dedicated gravity satellite missions (N-DGSMs) for the determination of temporal variations of geoid heights and bridging the gap between GRACE and GRACE-FO. The Amazon basin and the area of Poland were chosen as study areas. Monthly Global Geopotential Models (GGMs) developed using N-DGSMs data were utilized to determine temporal variations of geoid heights over the chosen study areas. Then, the obtained temporal variations of geoid heights were evaluated using ITSG-GRACE2016 GGMs. Time series of geoid height variations determined from GGMs of some N-DGSMs were smoothed using a moving average. The main findings reveal that for areas characterized with strong mass transport, e.g. the Amazon basin, correlation coefficients between smoothed temporal variations of geoid heights from GGMs of some NDGSMs and temporal variations of geoid heights from the ITSG-GRACE2016 GGMs reach the level of 0.6. For areas with a weak mass transport signal as for Poland, N-DGSMs-based GGMs investigated seem unsuitable for determining temporal variations of geoid heights.